Documentários de fronteira Brasil/Uruguai: marcas de identidades (in)comuns - Borba, Marcos Severino de (2014)
This study analyzes the construction of identity meaning in documentaries about border regions, especially the border between southern Brazil and Uruguay. Our research uses two documentaries produced in 2013, funded by Documenta Rio Grande of FAC RS (Support Fund for Culture of Rio Grande do Sul). Doble Chapa, by Leo Caobelli, presents the trajectory of two omniscient characters, one Brazilian and one Uruguayan, around the borders of the State represented by the demarcation landmarks of boundary. On the other hand, The Imaginary Line by Cíntia Langie and Rafael Andreazza exposes, from researchers and artists testimonies, a common and shared identity by the man of the pampas. Our theoretical path works with the documentary as a form of engagement in the world and borders as spaces for identity construction intertwined with an "other". Thus, we seek to understand whether these documentaries establish identity meaning differently from a hegemonic representation of the gaucho myth in the border between Rio Grande do Sul and Uruguay and also whether the public policies that promote the production of documentaries in the State allow other forms of representation of these identities, in opposition to the identity of the gaucho that is widespread in MTG and in the RBS group Communication. We will use as methodological tools film analysis and addition to literature and documental research. Our analysis points to an essentialist representation of the frontier and space as a generator of meaning in Doble Chapa and a hybrid, multi-faceted and dynamic marked by the presence of the subjects in the film A Linha Imaginária.